A Sociological Framework to Reduce Aberrant Behaviour of School Students Through Increasing School Connectedness. (July 2021) - Markham, Wolfgang A.; Dolan, Alan; Moore, Graham F.
A framework for understanding relationships between school connectedness and student aberrant behaviors is outlined that is synthesized from Merton's insights into anomie and Bernstein's theory of cultural transmission (which focuses on schools' instructional methods and students' internalization of schools' values). A seven-category classification system identifies students' risk of nonconformist behavior based upon students acceptance/rejection of dominant overarching cultural aspirations (commonly material prosperity); perception of schools' role in aspiration realization; responses to schools' instructional methods; and internalization of schools' values regarding conduct/character. We propose frustration weakens connectedness and is grounded in students' perceptions regarding their school's educational outcomes, degree of acceptance at school, and their school's values. We then consider student dispersal across schools, and how age may affect students' categorization and the influence of frustration risk factors. Finally, we discuss how initiatives within school organization, curriculum, and pedagogic practice may promote connectedness among different student categories and their potential adverse consequences.